2010
DOI: 10.5194/acp-10-9739-2010
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen oxides and PAN in plumes from boreal fires during ARCTAS-B and their impact on ozone: an integrated analysis of aircraft and satellite observations

Abstract: Abstract. We determine enhancement ratios for NO x , PAN, and other NO y species from boreal biomass burning using aircraft data obtained during the ARCTAS-B campaign and examine the impact of these emissions on tropospheric ozone in the Arctic. We find an initial emission factor for NO x of 1.06 g NO per kg dry matter (DM) burned, much lower than previous observations of boreal plumes, and also one third the value recommended for extratropical fires. Our analysis provides the first observational confirmation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
293
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(322 citation statements)
references
References 54 publications
28
293
1
Order By: Relevance
“…Boreal forest fires are also an important source of PAN and, due to their proximity to the Arctic, plumes can be transported to high latitudes during the spring and summer months (Brock et al, 2011;Singh et al, 2010). Whilst little O 3 production appears to occur close to boreal fires (Alvarado et al, 2010;Paris et al, 2010), several recent studies have shown O 3 production downwind from boreal fires in the Arctic during the summer months (Wespes et al, 2012;Parrington et al, 2012;Thomas et al, 2013). Nevertheless, O 3 production is higher in air masses influenced by anthropogenic emissions.…”
Section: Arcticmentioning
confidence: 96%
“…Boreal forest fires are also an important source of PAN and, due to their proximity to the Arctic, plumes can be transported to high latitudes during the spring and summer months (Brock et al, 2011;Singh et al, 2010). Whilst little O 3 production appears to occur close to boreal fires (Alvarado et al, 2010;Paris et al, 2010), several recent studies have shown O 3 production downwind from boreal fires in the Arctic during the summer months (Wespes et al, 2012;Parrington et al, 2012;Thomas et al, 2013). Nevertheless, O 3 production is higher in air masses influenced by anthropogenic emissions.…”
Section: Arcticmentioning
confidence: 96%
“…The increasingly negative enhancement ratios for O 3 in Ta-535 ble 1 indicate that it undergoes a destruction process within the plume in the first few days, the net decrease in concentration is most likely dominated by oxidation reactions with numerous short-lived primary pyrogenic species within the young plumes. It was also noted by Alvarado et al (2010) 540 that there was very little clear evidence for O 3 formation in the young boreal plumes measured during ARCTAS-B in either aircraft or satellite observations and suggested that this was due to 40% of the NO x from the fires being converted to PAN within a few hours of emission thus limiting the imme-545 diate reactivity of the plume. An in-depth review of the production of O 3 in wildfires was recently published by Jaffe and Wigder (2012).…”
Section: O 3 Production In Boreal Biomass Burningmentioning
confidence: 99%
“…NO 2 is also an important precursor to PAN which forms within a few hours. At low temperatures in the free troposphere, and in the presence of co-emitted NH 3 , HNO 3 will quickly convert to ammonium nitrate (NH 4 NO 3 ) (Yokelson et al, 2009;Alvarado et al, 2010). At night, NO 2 + O 3 can make NO 3 and NO 2 + NO 3 can make N 2 O 5 , which can hydrolyse to make HNO 3 .…”
Section: Enhancement Ratiosmentioning
confidence: 99%
“…There was an early and unusually strong fire source in this region in spring 2008 due to early snow melt, and the smoke was a source of both carbonaceous aerosols and O 3 precursors to the Arctic (Jacob et al, 2010;Warneke et al, 2009). PAN can form rapidly in boreal smoke plumes, with approximately 40 % of the initial NO x emissions converted to PAN within a few hours of emission (Alvarado et al, 2010). Plumes from the Lake Baikal area, containing PAN mixing ratios up to ∼500 pptv, were also observed at MBO during spring 2008 (Fischer et al, 2010b, see Fig.…”
Section: Variations In a Pan Source: Biomass Burning Emissionsmentioning
confidence: 99%